Targeting Regulatory Pathways Of Stim1 In Nasopharyngeal Cancer - Imakwu, Okekpa Simon (2021)
Stromal interaction molecule 1 (STIM1) is involved in various carcinogenic processes. However, the involvement and molecular implication of STIM1 in nasopharyngeal cancer (NPC) is not fully understood. This study aims to investigate the regulatory roles of STIM1 and associated signaling pathways in NPC, using a DsiRNA-mediated gene knockdown model. The NPC cell lines used were HK1/NPC-Non EBV- and C666-1/NPC EBV-related cells. Genes and related functional pathways were assessed through bioinformatics analysis. STIM1 expression and the transcriptional- and post-transcriptional effects of STIM1 knockdown in NPC cell lines were determined through RT-qPCR. The functional roles of STIM1 knockdown were studied in terms of cell proliferation, cell migration, colony formation ability, calcium profiles and reactive oxygen species activities. Then, the post-translational effect of STIM1 in NPC were studied through Western blot and immunohistochemical staining. Low STIM1 expression in HK1/NPC and high STIM1 expression in C666-1/NPC were observed because of differences in NPC tumour pathogenesis. Optimum STIM1 knockdown was achieved at 12 h and sustained for 72 h in HK1/NPC, whereas optimum STIM1 knockdown for C666-1/NPC was achieved at 48 h and sustained for 72 h. STIM1 knockdown regulated the expression of PIK3CA, AKT1, Orai1, BCL2 and SKP2, which were associated with NPC. STIM1 knockdown regulated the expression of BAX, P27, PTEN, RYR2, ATP2A2 and CDH1, which were associated with the inhibition of NPC. Our findings showed that STIM1 silencing can regulate the expression of miRNA 205-3p, miRNA 185-5P, mir-34a-5p, let-7b-5p, miRNA 200a- 3p and miRNA375 after transcription, indicating good prognosis.